TYPES AND FACTORS CAUSING PLAGIARISM IN PAPERS OF ENGLISH EDUCATION STUDENTS - Rizkariani Sulaiman (Universitas Sembilanbelas November Kolaka, 2018)
The purpose of this study is to determine the type of plagiarism contained in the student papers on the subject of Introduction to Literature and the factors causing students to do plagiarism. Researchers used descriptive quantitative research methods to answer both research questions. In this study, this type of plagiarism is examined using unpaid online applications and manuals to determine the type of plagiarism based on indicators of government regulation no. 17, 2010. While the factors causing plagiarism obtained through the responses of respondents to a given questionnaire. Population in research is one semester students majoring in English Education. The total population was 50 students and the sample in the study was 44. The results of the study show that type 1 plagiarism is the most dominant type appearing in student papers, followed by plagiarism types 2, 3 and 4. Chapters 1 and 2 in most papers are chapters where the chances of plagiarism occur most often. Then, the factors that cause students to practice plagiarism are: a) lack of understanding how to cite and write references well so not confident in composing academic writing; b) limited access to referrals and c) student attitudes which often delay and hasten in completing tasks.